Visual Performance Following Bilateral Implantation of Refractive Rotationally Asymmetric Bifocal Intraocular Lens (LS-313 MF30) or Apodized Diffractive Bifocal Intraocular Lens (ReSTOR SN6AD1) - Li H; Liu D; Gao H; Sun J; Bai H; Wu X (Dove Medical Press, 2021)
Honglei Li,1,2 Dongle Liu,1,2 Han Gao,3 Jiajun Sun,1,2 Huiran Bai,1,2 Xiaoming Wu1,2 1Qingdao Eye Hospital of Shandong First Medical University, Qingdao, People's Republic of China; 2State Key Laboratory Cultivation Base, Shandong Provincial Key Laboratory of Ophthalmology, Shandong Eye Institute, Shandong First Medical University & Shandong Academy of Medical Sciences, Qingdao, People's Republic of China; 3Department of Ophthalmology, Qingdao Central Hospital, The Second Affiliated Hospital of Medical College of Qingdao University, Qingdao, People's Republic of ChinaCorrespondence: Xiaoming WuQingdao Eye Hospital of Shandong First Medical University, 5 Yanerdao Road, Qingdao, 26600, People's Republic of ChinaEmail wuxiaominglmm@126.comPurpose: This study compared the clinical outcomes after cataract surgery with implantation of refractive rotationally asymmetric bifocal intraocular lens (IOL) (LS-313 MF30) and apodized diffractive bifocal IOL (ReSTOR SN6AD1).Methods: This was a prospective, non-randomized, controlled study, where patients diagnosed with age-related cataracts were selected for phacoemulsification combined with bilateral IOL implantation. Based on the type of IOL voluntarily implanted, the patients were divided into two groups, ie, refractive and diffractive groups. In total, 30 cases (60 eyes) were in a refractive group, while 30 cases (60 eyes) were in diffractive group. Three months after surgery, we examined the uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA), uncorrected near visual acuity (UNVA), defocus curve, objective visual quality, and subjective questionnaire.Results: Three months after surgery, the UIVA of the refractive group (0.18 ± 0.08) logMAR was better than that of the diffractive group (0.29 ± 0.16) logMAR (P < 0.05). No significant difference in UDVA and UNVA was noted between the two groups. For a 4mm pupil diameter, the intraocular and total eye aberration, higher-order aberration (HOA), coma, spherical aberration, and trefoil in the refractive group were significantly higher than those in diffractive group (P < 0.05). The intraocular modulation transfer function (MTF), intraocular strehl ratio (SR), total eye MTF, and total eye SR in the refractive group were lower than those in diffractive group (P < 0.05). No significant difference in glare incidence, spectacle independence rate, and patient satisfaction was observed between the two groups (P > 0.05). The halos incidence in the refractive group was lower than the diffractive group (P < 0.05).Conclusion: Both bifocal IOLs obtained satisfactory UDVA and UNVA, with higher patient satisfaction. Unlike the apodized diffractive bifocal IOL, the refractive rotationally asymmetric bifocal IOL yielded slightly better UIVA, lower halos incidence, whereas the apodized diffractive bifocal IOL showed a better objective visual quality.Keywords: refractive rotationally asymmetric, apodized diffractive, intraocular lens, visual quality